Penggunaan Metode K-Means dalam Data Mining untuk Identifikasi Pola Konsumsi Listrik pada Rumah Tangga - Silvia Lestari (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
Increasing electricity consumption in households is one of the problems faced by many countries, including Indonesia. This can lead to increased energy costs and negative environmental impacts. The K-Means method is one of the data mining methods that can be used to analyze electricity consumption patterns. This method works by grouping data into several groups based on the similarity of the pattern. By using the K-Means method, electricity consumption patterns in households can be better identified. This can provide valuable information to improve the efficiency of electricity use. This can help the government to formulate appropriate policies to improve the efficiency of electricity use in households.Electricity companies can use this method to identify electricity consumption patterns based on the type of equipment used. This can help electricity companies to develop more effective education programs to raise public awareness about the importance of saving energy. Thus, the K-Means method can be a useful tool to improve the efficiency of electricity use in households.